Association of Weight Status of Affluent Adolescents with the Family History of Chronic Diseases, Age, Gender, Birth Weight and Socio-Economic Status. - Asar, Farzana (Nurture, 2008)
Obesity is increasing among affluent people of the developing world, however underweight may still be present and both the problems needs to be assessed and addressed simultaneously. This study was conducted to assess the prevalence of underweight and overweight in the affluent urban adolescents of Karachi and study its association with family disease history and other factors. Data (socio demographic information, height & weight) was collected from 868 girls and 818 boys aged 10-15 years, studying in secondary section of the selected private schools known to have a high proportion of children from the affluent group. According to CDC standards 63% children had their BMI’s within normal ranges, 17% were underweight, 11.5 % were OW and 8% were Obese (BMI for age >95th percentile). Family disease history of chronic disease was associated with higher prevalence of obesity. Prevalence of both under and overweight among affluent adolescents needs to be addressed even among affluent children.